Prophetic repairs: Narrative and social action among Puerto Rican Taíno. (September 2017) - Feliciano-Santos, Sherina
Abstract: This article considers the sources of knowledge and frameworks of knowing from which Puerto Rican Taíno draw in order to support their identification as Taíno. Widespread, authoritative historical narratives of the Caribbean claim that the Taíno population was decimated between the 16th and 18th centuries. This analysis highlights the role that prophetic narratives and communicative strategies played in reframing and recalibrating Taíno historical tellings and in the refashioning of personal trajectories of social actors as Taíno. Highlights: The role of prophecy within indigenous reclamation and activism in Puerto Rico. Prophecy undermines historical narratives of Taíno extinction. Face to face interaction is a key site for socializing prophetic narratives and framing. Prophetic framing encourages identification and social action as Taíno social actors. Prophecy offers a form of narrative coherence, which can have powerful political implications for identitarian movements.